2014
DOI: 10.1111/nph.13012
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Male Sterility 2 function during spore and pollen wall development supports an evolutionarily early recruitment of a core component in the sporopollenin biosynthetic pathway

Abstract: SummaryThe early evolution of plants required the acquisition of a number of key adaptations to overcome physiological difficulties associated with survival on land. One of these was a tough sporopollenin wall that enclosed reproductive propagules and provided protection from desiccation and UV-B radiation. All land plants possess such walled spores (or their derived homologue, pollen).We took a reverse genetics approach, consisting of knock-out and complementation experiments to test the functional conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…For the ms2 mutant, PpMS2 driven by the MS2 promoter could not rescue its fertility. However, DPW driven by the MS2 promoter could rescue its fertility with normal pollen wall formation [32, 42]. These results suggested that DPW and MS2 have a very similar function, while PpMS2 and MS2 have evolutionary divergence.…”
Section: Discussionmentioning
confidence: 99%
“…For the ms2 mutant, PpMS2 driven by the MS2 promoter could not rescue its fertility. However, DPW driven by the MS2 promoter could rescue its fertility with normal pollen wall formation [32, 42]. These results suggested that DPW and MS2 have a very similar function, while PpMS2 and MS2 have evolutionary divergence.…”
Section: Discussionmentioning
confidence: 99%
“…WT strain “Gransden 2004”, used for genome sequencing 32 , provided the genetic background for the generation of Δ PpSCRM1 mutants (“Gransden 2004”, Freiburg) and ‘Villersexel’ the genetic background for the generation of Δ PpSMF1 mutants (Sheffield), and “Gransden D12” was the background for production of the Δ PpSMF2 mutants. P. patens was grown axenically on BCDAT medium 33 supplemented with 1 mM calcium chloride and overlaid with cellophane discs (AA Packaging, UK), in 9 cm Petri dishes sealed with Micropore tape (3M) in Sanyo MLR incubators under continuous light (140 μmol m −2 s −1 ) at 25 °C 34 . P. patens (Freiburg) was grown in liquid or on solid (12 g/L purified agar (OXOID, Thermo Scientific, Waltham, MA, USA)) supplemented Knop medium 35,36 and cultivated at 23 °C under a 16-hour light and 8-hour dark cycle 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Wallace et al reported that MS2 was an evolutionarily conserved core component in the sporopollenin biosynthetic pathway [64]. So, it raised our great interest in investigating the relationship between MS2 and male sterility in MT plants in our future research.…”
Section: Deps Related To Exine Formationmentioning
confidence: 98%